Bayesian Estimation of the Limiting Availability in the Presence of Right-Censored Data - Salinas-Torres, V; Romeo-Nunez, J (Springer-Verlag Italia s.r.l., 2014)
This work presents a Bayesian approach for estimating the limiting availability of an one-unit repairable system when the data are subject to right censorship. It is assumed that the failure and repair times of the components are independent exponential random variables. A conjugate Bayesian analysis is performed considering an informative and non informative prior distributions. Simulations are presented to study the performance of the Bayesian solutions. Some observations are made in relation to the maximum likelihood method. The Weibull case is also discussed. © 2014 Sapienza Università di Roma.